Socioeconomic Determinants and Their Interactions in Shaping Improved Sanitation Access in Indonesia - Gentur Jalunggono; Fitrah Sari Islami; Dinar Melani Hutajulu (Universitas Negeri Semarang, 2025)
Access to adequate sanitation facilities is a key agenda in Sustainable Development Goal (SDG) 6, but is still an urgent development issue in Indonesia. The equitable distribution of sanitation services between regions has not been fully achieved due to strong regional disparities, high levels of poverty, and ongoing socio-economic inequality. This study aims to analyze the socio-economic determinants that affect the level of community access to adequate sanitation facilities in Indonesia. The quantitative approach was used through regression analysis of panel data at the provincial level during the 2019-2023 period, utilizing secondary data sourced from the Central Statistics Agency (BPS) and the World Bank. The dependent variable in this study is the proportion of households that have access to proper sanitation facilities. Meanwhile, Gross Regional Domestic Product (GRDP), Gini ratio, poverty rate, and life expectancy are used as independent variables that represent the economic condition of the region, income distribution, social vulnerability, and the level of welfare of the population. The results show that the increase in regional GRDP has a positive and significant effect on sanitation access. Life expectancy also positively related to the availability of good sanitation. On the contrary, higher income inequality and a large prevalence of poverty have been shown to decrease people's chances of obtaining proper sanitation services.